Information and metrological support for the complex of robotic devices - Ашуров , А. Е.; Абдирашев , О. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article deals with the issue of modeling the lander’s motion in orbit. The article provides general information about the movement of the lander in the Earth’s atmosphere, a general image of the aerodynamic descent from orbit, and an idea of the equation of motion and ballistic trajectory. Equations and constant paths that systematize the mathematical model of motion in the lander orbit are considered. This article reveals the possibilities of application in the study of models of the lander and the search for new routes of the lander. If the amount of descent from orbit deviates from the base due to unforeseen technical reasons, the spacecraft may fall into a geographically inconvenient zone, if not into a populated area. On the way to ensure the safety of astronauts during their landing and in connection with the problem of protecting them from falling into localities of unexpected vehicles from space, their safety. Therefore, the study of the influence of atmospheric parameters on the movement of the unloading vehicle and improving the accuracy of its motion model is considered one of the most urgent problems of modern space science. The theoretical significance of the article is that it provides a solution to a system of real equations and uses a coefficient calculated from the International standard model of the atmosphere as a function of the distribution of air density over height.